2021
DOI: 10.1002/lary.29900
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia, Dysphonia, and Dysarthria Outcomes Among Adults Hospitalized With COVID‐19 Across Ireland

Abstract: Objective: To investigate the presence, degree, predictors, and trajectory of dysphagia, dysphonia, and dysarthria among adults hospitalized with COVID-19 across the Republic of Ireland (ROI) during the first wave of the pandemic.Study Design: Prospective observational cohort study. Methods: Adults with confirmed COVID-19 who were admitted into 14 participating acute hospitals across ROI and referred to speech and language therapy between March 1st and June 30th , 2020 were recruited. Outcomes obtained at init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 31 publications
1
35
1
1
Order By: Relevance
“…At the title and abstract review stage, the kappa coefficient was 0.81 and at the full article review stage the kappa coefficient was 0.90. As can be seen in Table 2, 17 out of the 54 publications provided empirical data [5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Most evidence was either Level IV (well-designed case-control or cohort studies) or VI (case study) and a grade of 'B' when applying the American Society of Plastic Surgeons grade recommendation scale for evidence-based clinical practice guidelines [26], meaning that empirical evidence is available and findings are consistent, but clinicians should remain alert to new information and patient preferences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At the title and abstract review stage, the kappa coefficient was 0.81 and at the full article review stage the kappa coefficient was 0.90. As can be seen in Table 2, 17 out of the 54 publications provided empirical data [5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Most evidence was either Level IV (well-designed case-control or cohort studies) or VI (case study) and a grade of 'B' when applying the American Society of Plastic Surgeons grade recommendation scale for evidence-based clinical practice guidelines [26], meaning that empirical evidence is available and findings are consistent, but clinicians should remain alert to new information and patient preferences.…”
Section: Resultsmentioning
confidence: 99%
“… With intensive therapy, most patients can regain normal swallow function following COVID-19. In a study conducted in the Republic of Ireland, Regan and colleagues [20] reported that postextubation, 90% of patients referred for a dysphagia assessment required altered oral intake, 36% were not allowed oral intake and 59% required tube feeding. In their analysis, age, proning and preexisting respiratory disease were predictors of oral intake status post-extubation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bei schweren Verläufen von Coronavirus-Erkrankungen 2019 (COVID) kann es neben den bekannten die Atmung betreffenden Komplikationen auch zu erheblichen Stimm- und Schluckstörungen kommen (zum Beispiel Critical-illness-Dysphagie oder Post-Extubations-Dyphagie) [ 1 – 3 ].…”
Section: Introductionunclassified